Experience of health professionals in care of the homeless population with tuberculosis - Tatiana Ferraz de Araújo Alecrim; Fernando Mitano; Amanda Alessandra dos Reis; Cristine Moraes Roos; Pedro Fredemir Palha; Simone Teresinha Protti-Zanatta
Abstract OBJECTIVE Analyzing statements of health professionals from a Street Clinic regarding care of a homeless population with tuberculosis. METHOD This is a qualitative research, conducted in the central region of São Paulo at three basic health units in the period of November to December 2014. A semi-structured interview guideline was implemented for data collection and all interviews were recorded using a digital recorder. RESULTS Six health professionals were interviewed. According to the Discourse Analysis perspective, three discursive segments emerged: experiences on care in the streets; weaknesses inherent to the treatment process; and incentives as a means of maintaining sick people in treatment. CONCLUSION Caring for a the homeless population with tuberculosis constitutes a new and challenging experience. It involves difficulties in dealing with the reality of a miserable social context, a lack and inadequacy of services, as well as care limitations for treatment and treatment dropout, which reinforces multiresistance. However, the investigated Street Clinic teams seek to expand access to health and social care services to this population.